PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MAKE A MATCH UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS III SDN 005 SUNGAI SEGAJAH KECAMATAN KUBU KABUPATEN ROKAN HILIR - Kartini Kartini; Lazim N Lazim N; Zulkifli Zulkifli (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The research is about the low science,s studies students learning outcomes with an average 56,25. While the value of minimum of criteria of completeness is 65. This researth is classroom action researth (CAR). That is suppose to increase the science,s studies students learning outcomes at fourth brrade of elementary school 005 Sungai Segajah Kubu in Rokan Hilir District. Formulation of this research is: Does the application of cooperative learning model type make a match can increase the learning outcomes of social studies at fourth grade of elementary school 005 Sungai Segajah Kubu in Rokan Hilir district. The students learning outcomes before CAR is about 56,25% in fair category. Whereas after CAR in cycle 1 increase about 66,25% with fairly good category ard in cycle II is about 71,25% with good category the comparison of students learning outcomes in before and after CAR in cycle I inerease about 17,77% whereas from cycle 1 to cycle 2 incerease about 26,66%. The teacher is activity has an average incycle 1 is about 62,25%. Whereas in cycle 2 is about 79,16%. And the students activity have an average value in cycle 1 is about 58,33% and cycle 2 is about 75%. The result of this research is the application of cooperative learning model type make a match can increase the science,s studies students learning outcomes at fourth brade of elementary school 005 Sungai Segajah Kubu in Rokan Hilir District.Key Word : Kooperative type make a match, The science,s students Achievement